Herodotus and the Presocratics : inquiry and intellectual culture in the fifth century BCE - Kingsley, K. Scarlett, 1984- (Cambridge University Press, 2024)
Herodotus' Histories was composed well before the genre of Greek historiography emerged as a distinct narrative enterprise. This book explores it within its fifth-century context alongside the extant fragments of Presocratic treatises as well as philosophizing tragedy and comedy. It argues for the Histories' competitive engagement with contemporary intellectual culture and demonstrates its ambition as an experimental prose work, tracing its responses to key debates on relativism, human nature, and epistemology. In addition to expanding the intellectual milieu of which the Histories is a part and restoring its place in Presocratic thought, K. Scarlett Kingsley elucidates fourth-century philosophy's subsequent engagement with the work. In doing so, she contributes to a revision of the sharp separation between the ancient genres of philosophy and history. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details.